2010
DOI: 10.1162/jocn.2009.21226
|View full text |Cite
|
Sign up to set email alerts
|

Transitive Inference: Distinct Contributions of Rostrolateral Prefrontal Cortex and the Hippocampus

Abstract: The capacity to reason about complex information is a central characteristic of human cognition. An important component of many reasoning tasks is the need to integrate multiple mental relations. Several researchers have argued that rostrolateral prefrontal cortex (RLPFC) plays a key role in relational integration. If this hypothesis is correct, then RLPFC should play a key role in transitive inference, which requires the integration of multiple relations to reach a conclusion. Thus far, however, neuroscientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 66 publications
9
94
0
Order By: Relevance
“…In contrast, activity in prefrontal cortex increases when secondorder relations must be integrated [36,35]. These findings and many others (e.g., [37,38]) have implicated the prefrontal cortex -or, more specifically, rostrolateral prefrontal cortex (RLPFC) -in higher-order relational reasoning.…”
Section: Neurodevelopment Of Reasoningmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, activity in prefrontal cortex increases when secondorder relations must be integrated [36,35]. These findings and many others (e.g., [37,38]) have implicated the prefrontal cortex -or, more specifically, rostrolateral prefrontal cortex (RLPFC) -in higher-order relational reasoning.…”
Section: Neurodevelopment Of Reasoningmentioning
confidence: 58%
“…Further, lateral parietal cortex is engaged more strongly when fMRI study participants represent ordered relations (e.g., x is larger than y) than associative relations (e.g., x and y are related) on a test of transitive inference [35] -i.e., when the nature of the relationships must be considered to solve the problem.…”
Section: Neurodevelopment Of Reasoningmentioning
confidence: 99%
“…This is what might be expected if the PPC and PFC processed spacetime interval inequalities. Wendelken and Bunge (2010) found that the extraction of mental relations from the hippocampus by the PPC and PFC initiates an important process of relational integration. These studies support the contention that entorhinal cortex grid cells provide a reference grid in the hippocampus for the representation of spacetime interval inequalities and that the PPC and PFC may preferentially extract these in a process of relational integration.…”
Section: Representation Of Spacetime Intervalsmentioning
confidence: 99%
“…As such, the creation of dreams and simulations of future events occur because the MTL can uniquely construct events using knowledge of the past. Specific evidence that the hippocampus and MTL are involved in fluid reasoning has been shown in tasks of relational reasoning and making transitive inferences (Greene et al 2006;Wendelken and Bunge 2010). Thus, this system would be ideally involved in a fluid process, such as critical-analytic thinking, in which one must create or construct new knowledge from episodes and concepts stored in memory.…”
Section: Declarative Memorymentioning
confidence: 99%
“…A neurobiological model of fluid reasoning has been proposed ) involving a network of brain regions: the left fronto-parietal system (including the left dorsolateral prefrontal cortex, DLPFC, and inferior parietal lobule, IPL) as well as the anterior pole of the frontal cortex known as the rostrolateral prefrontal cortex (RLPFC), which is thought to play a role in setting and executing complex abstract rules (Badre et al 2005;Koechlin and Summerfield 2007). These regions are ubiquitously activated across verbal and nonverbal analogy tasks ) and relational reasoning tasks (Wendelken and Bunge 2010), as well as matrix reasoning tasks (Crone et al 2009), yet the functions they subserve may be distinct.…”
Section: Fluid Reasoningmentioning
confidence: 99%